2015
DOI: 10.1002/cphc.201500118
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki Coupling Reactions Catalyzed by PdO Dispersed on Dealuminated Y Zeolite in Air under Ambient Conditions

Abstract: Suzuki coupling reactions are performed using PdO loaded on dealuminated Y (USY) zeolite. The reaction between bromobenzene and phenylboronic acid is complete in 15 min at room temperature in air, with a turnover number of 1300. The reaction can be repeated at least five times by using 1 wt % Pd. Inductively coupled plasma analysis does not reveal the dissolution of Pd from products, even if the reaction is repeated up to four times. Pd K-edge extended X-ray absorption fine structure analysis reveals the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…4−7 These catalysts are mostly based on the immobilization of palladium (Pd) nanoparticles on a solid support; the selection of supports has included silica, 8 alumina, 9,10 and zeolites. 11,12 Building upon the popular use of carbon as a support for Pd/C catalysts, recent studies have employed carbon nanomaterials in the design and fabrication of catalysts. 13−15 In fact, the heterogeneous catalyst consisting of Pd on graphite oxide (GO) exhibited activities nearly matching those of high-performance homogeneous catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4−7 These catalysts are mostly based on the immobilization of palladium (Pd) nanoparticles on a solid support; the selection of supports has included silica, 8 alumina, 9,10 and zeolites. 11,12 Building upon the popular use of carbon as a support for Pd/C catalysts, recent studies have employed carbon nanomaterials in the design and fabrication of catalysts. 13−15 In fact, the heterogeneous catalyst consisting of Pd on graphite oxide (GO) exhibited activities nearly matching those of high-performance homogeneous catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There have been many reports on Suzuki coupling reaction which proposing that the catalytic active site is a pd(0) species, and in cases where Pd(II) is applied this is the general believe that in situ reduction of Pd(II) to Pd(0) occurs during the reaction. On the basis of this mechanism, in catalytic systems where Pd and PdO and sometimes promoters such as NiO are present simultaneously, the conversion between PdO and Pd is the starting point in the Suzuki coupling reaction, and this has been stated as the equilibrium between PdO and Pd nanoparticles in the most of the published works up to date, and the presence of O 2 in the reaction media prevents the formation of Pd(0) with a tendency to agglomeration by shifting the equilibrium toward Pd(II) . Elaboration of this point of view might be informative because the nature of active sites on Pd for oxidative addition of aryl halide has remained as a subject of debates despite extensive research on the Suzuki‐Miyaura coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolites display catalytic activity on the C−C cross-coupling reaction when incorporated with not only Pd NPs and PdO. For example, Okumura and co-workers reported high catalytic activity of PdO dispersed on dealuminated ultrastable Y zeolites (PdO@USY) for Suzuki reactions; 154 PdO@USY catalyzed the reaction between bromobenzene and phenylboronic acid in 15 min at room temperature and retained its catalytic activity after repeated reaction without significant leaching. The authors observed that the fresh PdO@USY catalyst had a molecular-like PdO, whereas a mixture of Pd 0 −PdO existed in the used PdO@USY.…”
Section: Nanostructured Materials Supporting Pd Nanocatalystsmentioning
confidence: 99%